Images of the Self: Chastity Figures in the Faerie Queene - Garson, Joyce Marjorie (My University, 1977)
Since chastity, which as Spenser presents it seems to involve perception in an especially intense way, is one of the most complex virtues delineated in The Faerie Queene, the techniques which Spenser develops to define it are of particular interest. Partly because 'Diana' figures like Belphoebe and Britomart are surrounded by an aura of visual taboo, how they are seen and what they are able to see become aspects of the virtue which they represent. Since visually intense moments tend 'to stop the action' of the narrative, chastity becomes associated with images of static perfection; yet at the same time Spenser's heroines, embodying as they do almost masculine energy, seem to endow sheer forward momentum with moral significance. When Shakespeare deals with aspects of chastity in Venus and Adonis and The Rape of Lucrece, he too presents it in terms of paradoxes of stasis and development, insight and blindness: in the latter poem especialIy, the compulsion to define and project the self in the rhetoric of language and gesture issues in that thrust toward the iconic which I see as an important characteristic of Spenser's chastity figures. The 'iconic moment' is exemplified in The Faerie Queene in the first appearance of Belphoebe, whose virtue makes itself felt as a visual phenomenon and whose power is suggested by the way her image 'freezes' the narrative; as her story continues, however; the precise nature of the chastity which she represents is defined by a tension between stillness and development, isolation and involvement. Britomart, a more complex figure, comes to be defined in relation to the stasis associated specifically with art, the rhythm of her own story, with its headlong forward momentum, emerging in contrast to that of the narrative insets (like the myth of Venus and Adonis) which 'run down' into stillness and death. Her special strength, an intuitive ability to cut through complexities of erotic illusion which she never fully understands, is associated throughout Book III with her obliviousness to metaphorical language, which becomes linked with the erotic self-deception of other characters. Britomart's role in Book IV is discussed in relation to the major rhythm of that book, where the difficulty of social union is suggested by the way characters drift together and pull apart. In this context Britomart's power to unite becomes an important aspect of the virtue which she represents. Book V, where justice is seen to involve repression land oblivion is the appropriate context for the climax of Britomart'ls love-quest, which has raised from the beginning the questions of perception and of wholeness; the dream in Isis Church is analyzed in terms of the tension between involvement and detachment, image and process, insight and blindness, which have been important in her story from the beginning. In Book VI, Tristram, whose youthful purity is defined in the context of the tale of adult sexuality into which he intrudes and who like Belphoebe is a hunter whose glamorous image freezes narrative into icon, is discussed as a chastity figure whose treatment exemplifies some of the paradoxes which have been developed; in particular, the intensity of his visual presence initiates the tension between eye and ear which is significant throughout Book VI. Spenser's treatment of his chastity figures tends to involve the perceptions of the other characters and of the narrator and reader in a way which may well be called dramatic; the power of these characters to evoke some of the most effective narrative in the Faerie Queene derives from the nature of the virtue as Spenser conceives it.
Keywords: English Language and Literature; English Language and Literature